2013
DOI: 10.1161/circulationaha.113.001614
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Child and Adult Elevated Blood Pressure on Subclinical Atherosclerosis

Abstract: Background Elevated blood pressure (BP) levels in childhood have been associated with subsequent atherosclerosis. However, it is uncertain whether this risk is attenuated in individuals who acquire normal BP by adulthood. The present study examined the effect of child and adult BP levels on carotid artery intima-media thickness (cIMT) in adulthood. Methods and Results The cohort consisted of 4,210 participants from four prospective studies (mean follow-up 23 years). Childhood elevated BP was defined accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 238 publications
(179 citation statements)
references
References 41 publications
6
167
1
5
Order By: Relevance
“…Prospective studies have shown that elevated BP in adolescence is associated with both subclinical dysfunction of the left ventricle in the fifth decade of life and increased arterial stiffness (26)(27)(28)(29). Similarly, young adults with greater pulse wave velocity (PWV) had steeper increases of BP and visceral obesity from the age of 13 years (30).…”
Section: Relative Cardiovascular and Renal Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies have shown that elevated BP in adolescence is associated with both subclinical dysfunction of the left ventricle in the fifth decade of life and increased arterial stiffness (26)(27)(28)(29). Similarly, young adults with greater pulse wave velocity (PWV) had steeper increases of BP and visceral obesity from the age of 13 years (30).…”
Section: Relative Cardiovascular and Renal Riskmentioning
confidence: 99%
“…28 The effects of BP lowering treatment on renal function and disease in adults, especially in those with chronic renal disease, are still an area of dispute. A recent meta-analysis (177) has concluded for no significant effect on renal failure, but single studies have yielded discordant results, which may depend on the different nature of renal disease (e.g., diabetic or nondiabetic), presence or absence of proteinuria, and the type of BP-lowering agents (reninangiotensin system inhibitors vs other classes).…”
Section: Heartmentioning
confidence: 99%
“…The best evidence for rates of persistence of hypertension comes from the i3C cohort, a subgroup analysis of 1,602 children with elevated blood pressure from four prospective studies: the Bogalusa Heart Study, the Cardiovascular Risk in Young Finns Study, the Muscatine Study, and the CDAH study. Analysis showed that 60% (969/1602) of children with elevated blood pressure had continued blood pressure elevation as adults, and that improvement in blood pressure tracked most closely with decrease in BMI [31].…”
Section: Disease Management Overviewmentioning
confidence: 99%
“…In addition, elevated pulse pressure in youth has been associated with adverse changes in left ventricular morphology in youth and increased atherosclerosis in adulthood [11,45] . Most importantly, a recent study indicated that levels of carotid intima-media thickness (CIMT), a preclinical marker of atherosclerosis, is similar among those that normalize their elevated blood pressure in the time between youth and adulthood to those who did not have elevated blood pressure in youth or adulthood [58,59] . This reversal has not been demonstrated to the same extent in those who normalize their blood pressure during adulthood and thus confirms the importance of identifying elevated blood pressure in youth [41] .…”
Section: Importance Of Identifying Youth Hypertensionmentioning
confidence: 99%
“…For adiposity, the most comprehensive data were from Juhola et al [59] that used data from four large prospective studies (the Muscatine, Bogalusa, Young Finns and CDAH studies). They examined change in BMI z-score between youth and adulthood in respect to the youth-consumption, hormonal contraceptive use and socioeconomic status.…”
Section: Adulthoodmentioning
confidence: 99%